The Education of Medicinal Herb to The Member of PERLAHAT (Elderly Association Wants To Live A Healthy Life) - Wulandari, Ning Arti; Sari, Yeni Kartika; Setiyorini, Erni (Journal of Community Service for Health, 2020)
It is known that the older the person is, the lower organ function will be, and it cause some symptoms. Some elderly overcome these symptoms by drinking medicinal herbs, but they do not know for sure the benefits of it and the correct one to process it. The purpose of this research is to increase the knowledge of the elderly about medicinal plants. The method used was by giving education about medicinal herbs through lectures and demonstrations to 85 elderly students attending PERLAHAT activity. The pretest shows that the elderly knowledge about benefits, kind and way to process medicinal herbs gets 5,2 of mean and 10 for maximum point. The post test showed that after giving educational about medical herbs the means of elderly knowledge raises become 8,8 and 10 maximum point. It can be concluded that giving education about medicinal herbs through lecturer and demonstration suitable for elderly. Furthermore, nurses can not only giving education but also improves the utilization of medical herbs. So the elderly and families independency increase to overcome their health problem and improved their quality of life